Le tourisme interne, bouée de sauvetage en temps de crise ou locomotive du secteur touristique ? Cas du Maroc - Hassan Faouzi (Études Caribéennes)
This article discusses the changes that occurred in the tourism sector in Morocco during the Covid-19 pandemic and, on this basis, discusses the role that domestic tourism can play in facilitating tourism recovery and offsetting the decline in international tourism demand and its ability to initiate recovery. In the specific case of Morocco, the data suggest that during the crises, international travel was often replaced by domestic travel.